Characteristics of local COVID-19 cases aged ≥ 60 years in Zhejiang province during epidemic period dominantly due to SARS-CoV-2 Omicron variant infection - Bi-yao LIU; Zhen WANG; Xiao-hua QI (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To analyze the characteristics of local coronavirus disease 2019 (COVID-19) cases aged ≥ 60 years in Zhejiang province during the epidemic period dominantly due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant infection for providing evidence to the improvement of COVID-19 prevention and control among the elderly. MethodsThe information on all local COVID-19 cases aged ≥ 60 years at the diagnosis reported in Zhejiang province from March through April, 2022 were extracted from the National Information System for Disease Control and Prevention and from the reports of field surveys on the cases. Descriptive statistics were conducted to analyze epidemiological characteristics of the cases. ResultsOf a total of 163 elderly local COVID-19 cases reported during the two months, 82 (50.31%) were confirmed cases and 81 (49.69%) were asymptomatic infections. Among the 82 confirmed cases, 69 (84.15%) were mild type and 13 (15.85%) were common type; no severe/critical case and mortality were reported. For all the cases, the male to female ratio was 0.92 : 1; the age ranged from 60 to 95 years, with a median age of 68 years. The majority (69.33%, n = 113) of the cases' occupations were non-social workers. Nearly a half (46.01%, n = 75) of the cases had underlying diseases. More than a half (57.06%, n = 93) of the cases had full-dose COVID-19 vaccination with booster injection. Of the cases, 69.94% (114) were identified among the people under centralized medical observation. Among the cases with cardio-cerebrovascular diseases, the proportion of common type patients was significantly higher than that of asymptomatic infection compared with the cases without the diseases (P = 0.008). The proportion of common type COVID-19 was significantly lower than that of asymptomatic infection (P = 0.015) and mild type COVID-19 (P = 0.012) for the cases with booster COVID-19 vaccination in comparison with those without the booster vaccination. ConclusionThe clinical manifestation of local elderly COVID-19 cases was generally mild during the epidemic induced mainly by SARS-CoV-2 Omicron variant. The study results suggested that promoting COVID-19 vaccination and developing Omicron variant-specific vaccine are of significance for COVID-19 epidemic control and prevention in elderly population.